"Dreams of purple and hidden power": the romans women in the historiographical perspective of Maria José Hidalgo de La Vega (Ágora Journal, 2025)
Pudentilla, Zenobia, Agrippina, among many others, are characters who gain prominence in the historiography produced by Hidalgo de la Vega. In his works, women are understood as historical agents, regardless of the legal limitations imposed on them. Despite being deprived of political participation in the judiciary and public offices, prevented from having first names and at the mercy of the patria potestas of their male agnate relatives, they acted daily in the gaps left by power, manipulating the order in favor of their interests, often using subversive tactics to minimize their feminine position in a society that perceived them as inferior. Moving away from a conventional perspective that conceived Roman women as invisible, submissive and passive, Hidalgo de la Vega traces the thread of her historiographical narrative by positioning them as privileged actors of their destinies, breaking with the stereotype that identifies them as “victims or rebels” of an inescapable and absolute male domination.